ChemInform Abstract: A Highly Stereoselective Addition of Lithiated Ynamides to Ellman—Davis Chiral N‐tert‐Butanesulfinyl Imines. Issue 37 (22nd August 2013) - Wang, Xiao‐Na; Hsung, Richard P.; Qi, Rui; Fox, Sierra K.; Lv, Ming‐Can
Abstract The reaction of lithiated ynamides with the chiral sulfinyl imines is diastereoselective affording the products with the (S) configuration at the propargylic carbon.